Analysis of Millennial Moms Segmentation and Perceptual Mapping of Infant Formula Milk Market in Jakarta - Gunawan, Annetta; Glean, Raymond; Muchardie, Brian Garda (Binus Business Review, 2016)
The purpose of this research was to explore factors that influenced the millennial moms in making decision to purchase infant formula productand to use these factors as a basis to determine the segmentation of millennialmoms in the formula milk industry as well as the making of perceptual in formula milk industry in Jakarta. The used method was content analysis for the exploratory study whose data were collected through in-depthinterviews, cluster analysis and cross tabulation, as well as multidimensional scaling for descriptive research which data was obtained through the questionnaire. The obtained results indicate factors that affect the millennialmoms in selecting a formula milk, are price, nutrition, word of mouth, no side effects, taste, commercials, good result, brand loyalty, the recommendation from doctors, pure ingredients, compatibility with the childâs body, random trial and error. In addition, there are four market segments of millennial moms in infant formula milk market in Jakarta. There are medical-concern moms, well-educated moms, experience-based moms and randomtrial moms. Last, the perceptual mapping of formula milk brand in Jakarta shows five groups of brand according to the dimensions of economy-class of formula milk (economic vs premium) and variants of formula milk (plain vs. flavor).